Dual Graphitic‐N Doping in a Six‐Membered C‐Ring of Graphene‐Analogous Particles Enables an Efficient Electrocatalyst for the Hydrogen Evolution Reaction. (4th October 2019) - Lin, Zhiyu; Yang, Yang; Li, Mengsi; Huang, Hao; Hu, Wei; Cheng, Ling; Yan, Wensheng; Yu, Zhiwu; Mao, Kaitian; Xia, Guoliang; Lu, Jian; Jiang, Peng; et al.
Abstract: Graphene‐based materials still exhibit poor electrocatalytic activities for the hydrogen evolution reaction (HER) although they are considered to be the most promising electrocatalysts. We fabricated a graphene‐analogous material displaying exceptional activity towards the HER under acidic conditions with an overpotential (57 mV at 10 mA cm −2 ) and Tafel slope (44.6 mV dec −1 ) superior to previously reported graphene‐based materials, and even comparable to the state‐of‐the art Pt/C catalyst. X‐ray absorption near‐edge structure (XANES) and solid‐state NMR studies reveal that the distinct feature of its structure is dual graphitic‐N doping in a six‐membered carbon ring. Density functional theory (DFT) calculations show that the unique doped structure is beneficial for the activation of C−H bonds and to make the carbon atom bonded to two graphitic N atoms an active site for the HER. Abstract : Hoch dotiert : Graphen‐analoge Partikel mit dualer Dotierung durch graphitischen Stickstoff in einem sechsgliedrigen Kohlenstoffring wurden erfolgreich hergestellt. Mittels IR‐Spektroskopie, Synchrotron‐basierter Röntgenabsorptionsspektroskopie und Festkörper‐NMR werden ihre Struktur und der Mechanismus der Wasserstoffentwicklungsreaktion untersucht, wobei eine Stromdichte von 10 mA cm −2 bei einer Überspannung von 57 mV erreicht wird.